PENGUASAAN KEMBALI UNIT SEWA PEMBIAYAAN BERDASARKAN POJK 35 TAHUN 2018 - Nainggolan, Binsar; Nurbaiti, Siti (Tribuere, 2024)
Re-possession of finance lease units due to debtor default often raises complex legal issues, especially regarding the fulfilment of the rights of finance companies and how regulations exist in maintaining these rights, especially considering the protection of consumers. This research aims to analyse the re-control of the finance lease unit in POJK Number 35 of 2018 concerning the Implementation of the Financing Company Business and how the procedure for re-controlling the finance lease unit is carried out. The research uses normative juridical method with POJK Number 35 of 2018 regulatory approach and how the process of re-controlling the finance lease unit is carried out at PT HFI. Data obtained from PT HFI as the subject of research, The results showed that POJK Number 35 of 2018 has regulated the mechanism but needs a more detailed description and in its implementation PT HFI has fully complied with all regulations.